UPAYA GURU AKIDAH AKHLAK DALAM MEMBINA AKHLAK SISWA DI MAN 1 PADANG - Harvius Harvius (IAIN Padangsidimpuan, 2018)
This research is to find the efforts of the teachers of Akidah Akhlak in guiding the students’ akhlak in and out side of the classroom, to explore the problems in guiding, and to give the solution for the problems. The method of the research is descriptive qualitative with the informan are the teacher of Akidah Akhlak, the Headmaster, teachers, and students. The instruments are collecting the data by using observation, interview, and documentation. The result showed that the teachers guided the students to have good akhlak by explaining the materials well, showing the examples, avoiding the students to cheated in examination, giving advises to be serious in learning, and giving an educated punishment to the students’ falsity. Outside of the classroom, the teachers give the examples, praying zuhur together, giving kultum (preaching for 7 minutes), flag ceremonial, joining for the religious activities, cooperating with all teachers. Then, the problems are less carefulness from the teachers with the parents, unwell environment, absence from joining the religious activities, and choosing ungood friends. The efforst done by the teachers are cooperated raisingly between schools, teachers, parents, and societies. The teachers give pressure for the lesson, and give attention to the akhlak of the students. The teachers also must give good examples for the students, and give advises for them who had bad akhlak, and give advices for the parents to give attention to their children not to get bad environment and bad friends in order to be good children to make their akhlak better